The extension of sophisticated broadband and regional competitiveness – the case of västra götaland in Sweden - Sten Lorentzon (Netcom)
This paper focuses access to ”wired” broadband at businesses located to the periphery in the West of Sweden. The issue concerns regional competitiveness related to the prerequisites of using sophisticated ICT. The modern society of knowledge and competence, built up by presence in networks of information flows and nodes, emphasizes the influence of the individuals as decision-makers at location of activities. Furthermore, this paper pays attention to the need for exchange of unstructured information stressing the importance of face-to-face contacts and the access to meeting places.